Decade of progress in motor functional neurological disorder: continuing the momentum. Issue 6 (15th March 2021) - Perez, David L; Edwards, Mark J; Nielsen, Glenn; Kozlowska, Kasia; Hallett, Mark; LaFrance, Jr, W Curt
Abstract : Functional neurological disorder (FND) is a prevalent, disabling and costly condition at the neurology–psychiatry intersection. After being marginalised in the late 20th century, there has been renewed interest in this field. In this article, we review advances that have occurred over the past decade (2011–2020) across diagnosis, mechanisms, aetiologies, treatments and stigma in patients with motor FND (mFND, that is, functional movement disorder and functional limb weakness). In each content area, we also discuss the implications of recent advances and suggest future directions that will help continue the momentum of the past decade. In diagnosis, a major advance has been the emphasis on rule-in physical signs that are specific for hyperkinetic and hypokinetic functional motor symptoms. Mechanistically, greater importance has been given to determining 'how' functional neurological symptoms develop, highlighting roles for misdirected attention, expectation and self-agency, as well as abnormal influences of emotion/threat processing brain areas on motor control circuits. Aetiologically, while roles for adverse life experiences remain of interest in mFND, there is recognition of other aetiologic contributors, and efforts are needed to investigate links between aetiological factors and mechanisms. This decade has seen the first randomised controlled trials for physiotherapy, multidisciplinary rehabilitation and psychotherapy performed in the field, with consensus recommendations for physiotherapy, occupational therapy and outcome measures also published. Across patients, clinicians, healthcare systems and society, stigma remains a major concern. While challenges persist, a patient-centred integrated clinical neuroscience approach is primed to carry forward the momentum of the past decade into the future.